CEO Characteristics and Green Innovation: A Systematic Literature Review - Nurul Fitriani; Selma Putri Safira; Putri Dwi Aprilia Nur Khasanah; Yulianti Raharjo (Pusat P2M Politeknik Negeri Batam, 2024)
This study employs a systematic literature analysis to identify research gaps and opportunities on the influence of CEO qualities on green innovation. By critically evaluating the shortcomings of current research and synthesizing pieces from reliable, Scopus-indexed journals, it adds to the body of knowledge on green innovation. The study's conclusions point out gaps in the literature, pointing out that prior studies have mainly concentrated on green innovation in industrialized countries